The Effect of Communication Language Anxiety and Prior Learning Experience on Speaking Challenges and Strategies: The Case of Libyan Students in Malaysian Higher Education Institutions - Ali Salim Halali, Ahlam; Ismail, Lilliati; Abd Samad, Arshad; Bakar Razali, Abu; Noordin, Nooreen (Journal of International Students, 2023)
Libyan students’ academic speaking challenges associated with language anxiety and lack of English prior learning experience could impede Libyan students’ communication abilities in international academic setting. Students need to develop certain learning strategies for academic speaking in response to these factors. Therefore, explanatory mixed-mode research design, the researcher conducted an online questionnaire with 223 respondents, followed by interviews with 15 informants and a focused group discussion. Field notes and member checks were also carried out for triangulation and validation. SPSS, NVivo, and AMOS analyses carried out were correlational procedures and structural equation modelling (SEM) using bootstrapping resampling analyses to investigate the relationships between variables, determine the validity of study models, and test the research hypotheses. It was found that academic speaking strategies are influenced by language challenges when communication language anxiety and prior learning experience mediate the effects of speaking challenges and the implementation of strategies meant to overcome them.